SPOILING CHILDREN AND IMAGES OF GRANDPARENT’S CHILDCARE - Naning Yuliani; I’in Kalimatus Sa’diyah; Asmawati (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
Children's behavior is often associated with parenting patterns within the family, which will certainly be highlighted if the child's behavior does not conform to the norms in the family environment. Furthermore, the popular proverb in our society,